2012
DOI: 10.1158/1541-7786.mcr-11-0347
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Is an Important Factor that Maintains Cellular Immaturity and Contributes to Aggressiveness of Osteosarcoma

Abstract: Osteosarcoma is the most frequent, nonhematopoietic, primary malignant tumor of bone. Histopathologically, osteosarcoma is characterized by complex mixtures of different cell types with bone formation. The role of environmental factors in the formation of such a complicated tissue structure as osteosarcoma remains to be elucidated. Here, a newly established murine osteosarcoma model was used to clarify the roles of environmental factors such as fibroblast growth factor-2 (Fgf2) or leukemia-inhibitory factor (L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 48 publications
4
44
0
Order By: Relevance
“…14,22-25 FGF2 produced by tumorassociating fibroblasts reportedly contributes to maintain cellular immaturity and aggressiveness. 23 Interestingly, we found that inhibition of osteoblastic differentiation by TNFa or IL-1 through ERK was required for AX cell tumorigenesis through the maintenance of an undifferentiated state. Although IL-6 is an inflammatory cytokine implicated in tumorigenesis of various cancers, 15,16 IL-6 was not required for tumor development in this osteosarcoma model.…”
Section: Discussionmentioning
confidence: 85%
“…14,22-25 FGF2 produced by tumorassociating fibroblasts reportedly contributes to maintain cellular immaturity and aggressiveness. 23 Interestingly, we found that inhibition of osteoblastic differentiation by TNFa or IL-1 through ERK was required for AX cell tumorigenesis through the maintenance of an undifferentiated state. Although IL-6 is an inflammatory cytokine implicated in tumorigenesis of various cancers, 15,16 IL-6 was not required for tumor development in this osteosarcoma model.…”
Section: Discussionmentioning
confidence: 85%
“…The abundance of target mRNAs was determined relative to that of ACTB mRNA. For mouse samples, total RNA extraction, reverse transcription, and real-time PCR analysis was performed as described previously (12). Sets of primers for real-time PCR are listed in Supplementary Table S1.…”
Section: Reverse Transcription-pcrmentioning
confidence: 99%
“…For preparation of a tumor homogenate, small fragments were suspended in the same buffer and disrupted using Biomasher (Nippi) and ultrasonic treatment. Immunoblot analysis was performed as previously described (11,12). Actin or a-tubulin was examined as a loading control.…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 2 more Smart Citations